2017
DOI: 10.1093/dote/dox097
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-study on the feasibility of sentinel node navigation surgery in combination with thoracolaparoscopic lymphadenectomy without esophagectomy in early esophageal adenocarcinoma patients

Abstract: High-risk submucosal esophageal adenocarcinoma's might be treated curatively by means of radical endoscopic resection, followed by thoracolaparoscopic lymphadenectomy without concomitant esophagectomy. A preclinical study has shown the feasibility and safety of this approach; however, no studies are performed in a clinical setting. In addition, sentinel node navigation surgery could be valuable in tailoring the extent of the lymphadenectomy. This study aimed to evaluate the feasibility and safety of thoracolap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…To date, fewer studies have shown the feasibility and validity of the SN concept in esophageal cancer compared with studies on gastric cancer (Table ). However, a number of single institution studies have indicated acceptable outcomes of SN mapping and biopsy for early‐stage esophageal cancer .…”
Section: Results Of Sn Mapping In Esophageal Cancermentioning
confidence: 99%
“…To date, fewer studies have shown the feasibility and validity of the SN concept in esophageal cancer compared with studies on gastric cancer (Table ). However, a number of single institution studies have indicated acceptable outcomes of SN mapping and biopsy for early‐stage esophageal cancer .…”
Section: Results Of Sn Mapping In Esophageal Cancermentioning
confidence: 99%
“…The extent of nodal dissection can be further improved by near-infrared (NIR) fluorescent imaging modalities that are standardly integrated into the latest robotic platforms. This visual support can identify lymph nodes when a patient's tumor is injected preoperatively with labeled colloid or also preoperatively with indocyanine green (ICG) dye (47). Of course, it should be mentioned that conventional minimally invasive cameras are also available with NIR fluorescent imaging modes.…”
Section: Lymphadenectomy In Ramiementioning
confidence: 99%
“…The newest robotic systems offer technological improvements that will further enhance the surgeon's capabilities. Fluorescence cameras are now standard features on these systems and will allow visualization of the vascularization of the gastric conduit but possibly also help us to improve lymph node dissection and target sentinel nodes . Furthermore, a robotic 45‐mm stapler (EndoWrist® Stapler System, Intuitive Surgical, Sunnyvale, CA) was recently developed for use with the da Vinci Xi® Surgical System.…”
Section: Robotic Esophagectomymentioning
confidence: 99%
“…Fluorescence cameras are now standard features on these systems and will allow visualization of the vascularization of the gastric conduit but possibly also help us to improve lymph node dissection and target sentinel nodes. 46,47 Furthermore, a robotic 45-mm stapler (EndoWrist R Stapler System, Intuitive Surgical, Sunnyvale, CA) was recently developed for use with the da Vinci Xi R Surgical System. This stapler offers extended articulation (108°total side-to-side and 54°total up and down), and is equipped with force feedback.…”
Section: Robotic Esophagectomymentioning
confidence: 99%